ChemInform Abstract: A [2 + 2 + 2] Cyclization Strategy for the Synthesis of Phosphorus Embedding [6]Helicene‐Like Structures. Issue 21 (27th May 2014) - Aillard, Paul; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract Starting from the at the phosphorus atom (S)‐configured molecule (III), the product ratio of the helical stereoisomers (IV) is 33:67 (P:M).